Influence of Customer Perception in Selecting Hotels in Madurai Region - J.Prabhu,; Ravindran, K. (The journal of contemporary issues in business and government, 2021)
Over a decade hospitality industry showed a tremendous growth and it needs an update every day to attract the guests to with stand along with their competitors as well as the perception of guests are also changing every day to select a particular hotel. This perception is based on many things and also it changing for one place to another. Hence the hotel industry needs to be aware of the customer perception for their location. This paper will discuss about some common perception what the customers look into for selecting hotels in Madurai region.